2017
DOI: 10.1007/s00705-017-3303-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of natural co-infection with PCV2b subtypes in vivo

Abstract: Porcine circovirus type 2 (PCV2) is the causative pathogen of porcine circovirus-associated diseases (PCVAD). This virus evolves mostly through point mutations and genome recombination between different PCV2 genotypes (e.g. PCV2a and PCV2b), as has been confirmed in swine herds. In the current work, the complete PCV2 genome sequences of 69 clones derived from various tissues (lymph node, spleen and lung,) of an infected individual, were subjected to phylogenetic and alignment analyses. The results not only dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In this regard, we, in a previous study, not only confirmed the individual animal or the individual organ from this animal co-infected with diverse PCV2 genotypes, or even sub-genotypes, but also provided evidence of diverse point mutations acquired during immune escape by PCV2. Additionally, we noticed that the occurrence of point mutations exists in both ORF1 and ORF2 of PCV2 [24], as consistent with previous reports [25, 26]. However, the biological importance and significance of novel amino acid alterations, especially those in ORF1, are less characterized and explored.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this regard, we, in a previous study, not only confirmed the individual animal or the individual organ from this animal co-infected with diverse PCV2 genotypes, or even sub-genotypes, but also provided evidence of diverse point mutations acquired during immune escape by PCV2. Additionally, we noticed that the occurrence of point mutations exists in both ORF1 and ORF2 of PCV2 [24], as consistent with previous reports [25, 26]. However, the biological importance and significance of novel amino acid alterations, especially those in ORF1, are less characterized and explored.…”
Section: Introductionsupporting
confidence: 88%
“…The collection of clinical samples (spleen, lymph node, and lung) and the preparation of genomic DNAs have been described previously. The presence of PCV2 was identified by PCR using a forward primer ZY009 and a reverse primer ZY010 (Table 1) [24]. PCR amplification was initiated by preheating at 94 °C for 5 min, followed by 30 cycles at 94 °C for 30 s, 60 °C for 30 s, and 72 °C for 45 s, and a final extension at 72 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the exact mechanisms of PCVD/PCVAD are currently unknown [2]. However, many studies have reported co-infection with other swine pathogens, such as porcine reproductive and respiratory syndrome virus, porcine parvovirus, swine influenza virus, Mycoplasma hyopneumoniae , and Salmonella spp., are important cofactors that may enhance PCV2 infection and the severity of PCVD/PDVAD [2,6,7,8,9,10,11,12,13,14,15]. Furthermore, vaccination failure, stress or crowding together with PCV2-infected animals also cause PCVD/PCVAD [5,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Circovirus infections may play a role in autoimmunity by changing the homeostatic balance of proinflammatory cytokines and the immune system, indirectly affecting the severity of diseases caused by other pathogens (Opriessnig and Halbur 2012;Shulman and Davidson 2017). Previous studies have reported that concurrent infection of circovirus and other pathogens can result in serious immunosuppression and secondary infection (Gillespie et al 2009;Yi and Liu 2010;Zhai et al 2011;Opriessnig and Halbur 2012;Meng 2013;Sun et al 2015;Yang et al 2015;Ren et al 2016;Hu et al 2017). To date, little is known about natural MiCV infection in foxes and raccoon dogs and about coinfection with other pathogens.…”
mentioning
confidence: 99%